Down-regulation of 21A Alu RNA as a tool to boost proliferation maintaining the tissue regeneration potential of progenitor cells. Issue 18 (16th September 2016) - Gigoni, Arianna; Costa, Delfina; Gaetani, Massimiliano; Tasso, Roberta; Villa, Federico; Florio, Tullio; Pagano, Aldo
ABSTRACT: 21A is an Alu non-coding (nc) RNA transcribed by RNA polymerase (pol) III. While investigating the biological role of 21A ncRNA we documented an inverse correlation between its expression level and the rate of cell proliferation. The downregulation of this ncRNA not only caused a boost in cell proliferation, but was also associated to a transient cell dedifferentiation, suggesting a possible involvement of this RNA in cell dedifferentiation/reprogramming. In this study, we explored the possibility to enhance proliferation and dedifferentiation of cells of interest, by 21A down-regulation, using a mixture of chemically modified Anti-21A RNAs. Our results confirmed the validity of this approach that allows the amplification of specific cell populations, in a controlled manner and without inducing permanent effects. In addition to induce cell proliferation, the procedure did not decrease the tissue regeneration potential of progenitor cells in two different cell systems.